The transgenerational sustainability of family firms - Erdoğan, Irmak. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
Given the economic significance of family firms and their low rates of survival, understanding the factors that contribute to the transgenerational sustainability of family firms has been an important subject of research. In this dissertation, the topic of transgenerational sustainability of family firms is explored in light of three research studies conducted in Turkey. In Chapter 1, the significance of the topic is explained, and three research studies are introduced. In Chapter 2, the construct of commitment is explored in the context of next-generation members of the family firm. Based on in-depth interviews with 22 members of 17 long-lived family firms in Turkey, a model to explain the distinctive nature of commitment, as well as the roots of commitment in childhood and adolescence is developed. In Chapter 3, following an alternative approach to the study of transgenerational sustainability, the focus is on the entrepreneurial behavior of family firms. The purpose of this chapter is to explore the different ways in which long-lived family firms manage to be innovative while remaining firmly anchored to their traditions. In Chapter 4, through a survey among 252 owner-managers of family firms in Turkey, the effects of family social capital on owner manager’s intention for transgenerational sustainability are investigated. In Chapter 5, findings of three research studies are integrated and conclusions are drawn. Through combining different research methods and alternative approaches to the research topic, this dissertation aims to enhance our understanding of the factors that contribute to the transgenerational sustainability of family firms.
Keywords: Family-owned business enterprises.; Family-owned business enterprises -- Turkey.